TRADISI MOLO SABUANG MASYARAKAT MARAFENFEN DI KABUPATEN KEPULAUAN ARU, MALUKU - Welliken K, Marius Agustinus (Sabda: Jurnal Kajian Kebudayaan, 2017)
The customary tradition of â€œmolo sabuangâ€ is one of the ways used by indigenous people in Aru in resolving disputes or conflicts of Ownership Rights such as land boundaries, sea boundaries and plant boundaries. The implementation of â€œmolo sabuangâ€ is a form of local wisdom of the community of Aru in Maluku, which serves to create a social order, and potentially has a spirit value to create peace based on local culture. â€œmolo sabuangâ€ tradition is one of the cultures passed down from generation to generation from ancestors to descendants in Aru Island District. â€œmolo sabuangâ€ is a dive without a breathing apparatus while holding on a pole that is plugged in the water. This custom can solve the domestic problems that occur in the Aru society. This custom belongs not only to the Marafenfen community but also to of all the Aru indigenous people scattered from the north to the south